Knowledge and Attitudes of Health Science and Non-Health Sciences in the Use of Antibiotics in DKI Jakarta Province and Their Review from Islamic Perspectives - Riska Afrilia; Riyani Wikaningrum; Irwandi Zein (Junior Medical Journal, 2023)
Background: Antibiotics are used to treat infectious diseases caused by bacteria, but because of the public's perception that killing antibiotics can be used for all diseases, and the easy access to antibiotics due to poor supervision causes the rationality of using antibiotics to be doubted. Antibiotics used not according to the rules will cause serious problems such as side effects of these drugs and antibiotic resistance.Methods: The method used is by distributing questionnaires to health and non-health sciences in DKI Jakarta Province. The number of samples is 161 people using stratified sampling technique.Results: The results showed that in the knowledge category, health sciences had good knowledge of 33%, while non-health sciences had good knowledge of 6.6%. From the overall cross tabulation of 161 people, the majority of respondents had a good level of knowledge and a positive attitude of 81.1%.Conclusion: The conclusion in this study is that health sciences have more broad insight to use antibiotics better when compared to non-health sciences. The ability of health professionals must be strengthened to prescribe and administer antibiotics appropriately and to communicate effectively with patients. Governments should promote specific information on the rational use of antibiotics and AMR to certain target groups.